Environmental belief of students in higher technical educational institutions – the path to harmonious relationship between technogenic society and nature - Skrotska, Oksana; Voloshina, Iryna; Krasinko, Victoria; Lych (Tkachenko), Inna; Teterina, Svitlana (My University, 2011)
The article is devoted to the consideration of ways of the topical problems decision which get in way of harmonization of relations between technogenic society and the nature. It also devoted to the analysis of state of training of specialists on ecological orientation in the higher technical educational institutions.
Keywords: technogenic society; техногенне суспільство; техногенное общество; ecologization of manufactures; ecobiotechnology; bioenergetics; training of specialists; екологізація виробництв; екобіотехнологія; біоенергетика; підготовка фахівців; экологизация производств; экобиотехнология; биоэнергетика; подготовка специалистов; кафедра біотехнології і мікробіології